Occupational stress and environmental impact among traffic police officers in Kathmandu Valley, Nepal: A qualitative study. - Binita Yadav; Sandesh Bhusal; Anil K C; Pranil Man Singh Pradhan (Public Library of Science (PLoS), 2023)
Policing is considered an extremely stressful, physically demanding, and mentally challenging occupation. The growing population with an increasing number of vehicles and the harsh working environment has made the work of traffic police even more stressful. This qualitative study aims to examine work and environment-related stressful factors among traffic police officials of Kathmandu Valley, Nepal. This qualitative study used a thematic analysis approach. Face-to-face interviews were conducted with different cadres of 15 traffic police personnel working in Kathmandu Valley, Nepal for at least six months. The study adhered to the Consolidated Criteria for Reporting Qualitative Studies (COREQ) guideline. The findings of this study are structured around five major themes- workload, work-life balance, basic amenities, work environment and occupational health problems, and possible solutions and suggestions. Most of the participants (10 out of 15) reported having work stress due to the heavy workload and hazardous working conditions that had a significant impact on their job performance and mental well-being. This study highlights the challenges faced by traffic police officers in Kathmandu Valley, Nepal. The findings suggest that efforts should be made to improve the working environment of traffic police officers to reduce the physical as well as mental burden among them. The occupational health and safety (OHS) and mental well-being of traffic enforcers' is a critical public health issue, therefore, it should be on the agenda of policymakers, organizational leaders, and stakeholders.